EXTH-05. THERAPEUTIC IMPLICATIONS OF TTFIELDS INDUCED DNA DAMAGE AND REPLICATION STRESS IN NOVEL COMBINATIONS FOR CANCER TREATMENT. (11th November 2019) - Kumar Karanam, Narasimha; Ding, Lianghao; Aroumougame, Asaithamby; Story, Michael
Abstract: TTFields are low-intensity, intermediate frequency, alternating electric fields which are applied to tumor regions using non-invasive arrays. TTFields is approved for the treatment of glioblastoma and mesothelioma with clinical trials ongoing in other cancer types. The mechanism of action for TTFields includes interference with mitosis, reduced DNA double strand break (DSB) repair capacity and the frank induction of DNA DSBs. The mechanism by which TTFields induces DNA DSBs appears to be through the enhancement of DNA replication stress with continued TTFields exposure. The induction of DNA DSBs appears to be as a result of significantly reduced expression of the DNA replication complex genes MCM6 and MCM10 as well as the Fanconi's Anemia (FA) pathway genes. TTFields treatment increases the number of RPA foci, decreases nascent DNA length and increases R-loop formation which are markers of DNA replication stress. These results suggest that TTFields-induced replication stress is the underlying mechanism and cellular endogenous source of DNA DSB generation via replication fork collapse. The current study suggests that TTFields exposure causes a conditional vulnerability environment that renders cells more susceptible to chemotherapeutic agents that induce DNA damage and/or cause replication stress. Supporting this is the synergistic cell killing seen with TTFields exposure concomitant with cisplatin, TTFields plus concomitant PARP inhibition with or without subsequent radiation, or radiation given at the completion of a TTFields exposure. Finally, TTFields-induced mitotic aberrations and DNA damage/replication stress events, although intimately linked to one another as one can expose the other, are likely initiated independently of one another as suggested by the gene expression analysis of 47 key mitosis regulator genes. These results establish that enhanced replication stress and reduced DNA repair capacity are also major mechanisms of TTFields effects, effects for which there are therapeutic implications.